A framework for information technology outsourcing risk management - Aubert, Benoit A.; Patry, Michel; Rivard, Suzanne (ACM SIGMIS Database: the DATABASE for Advances in Information Systems, 2005)
This paper takes stock from several studies on Information Technology outsourcing risk. A definition of risk is offered, and an illustration from five case studies is used to show how risk can be managed. Results show that an active risk management approach can reduce risk exposure substantially while enabling the organizations to still reap the benefits associated with outsourcing.